Does the Inflation, Interest Rates, and Global Gold Price affect Islamic and Conventional Bank Stock Prices? - Saputra, Deky Candra; Rusgianto, Sulistya; Awaludin, Azrul Afrillana; Kurniawan , Eko (Jurnal Ekonomi Pembangunan, 2024)
The dynamic relationship between macroeconomic conditions, global gold prices, and stock market performance has been a major focus in various studies. This study investigates the impact of inflation, BI rates, and gold prices on the stock prices of Islamic and conventional banks in Indonesia. Using monthly data from January 2021 to December 2023. The method employed panel data regression using the Random Effect Model. The findings indicate that inflation has a negative and significant impact on the Islamic banks stock prices, while BI rates has insignificant effect. On the other hand, inflation has a positive and significant effect on the conventional banks’ stock prices, along with BI rates also having a positive and significant impact. However, global gold prices do not have a significant effect on the stock prices of either Islamic or conventional banks. These results provide deeper insights into how macroeconomic factors influence the performance of the stock market for Islamic and conventional banks in Indonesia.